Personal best time, not anthropometry or training volume, is associated with total race time in a triple iron triathlon - Knechtle, B.; Knechtle, P.; Rosemann, T.; Senn, O. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to investigate in 81 male recreational ultratriathletes (64 finishers and 17 nonfinishers) the relationship of anthropometry, prerace experience, and training with race outcome in a Triple Iron triathlon, using bi and multivariate analyses. In the bivariate analysis, the sum of 8 skinfolds (r = 0.38) and the sum of upper body skinfolds (r = 0.37) were positively related to total race time. None of the anthropometric variables was related to the swim or bike split. Circumference of upper arm (r = 0.42), percent body fat (r = 0.43), the sum of 8 skinfolds (r = 0.47), and the sum of upper body skinfolds (r = 0.45) were positively associated with the time in the run split. None of the training variables was related to total race time or split times. Personal best time in an Ironman triathlon (r = 0.59) and a Triple Iron triathlon (r = 0.82) were positively and highly significantly related to total race time. When all significant variables after bivariate analysis were included in a regression model, personal best time in a Triple Iron triathlon (p < 0.0001) remained the single predictor variable. For practical considerations, athletes with a background as an ultrarunner might have an advantage in successfully finishing a Triple Iron triathlon. However, ultrarunners should also have enough prerace experience in competing in Ironman and Triple Iron triathlons to successfully finish such a race.